Life satisfaction among sports participants: A systematic review - Sepdanius, Endang; Mohd Sidi, Adli Bin; Afriani, Rini; Saputra, Endarman; Hasim, Mustakim (SPORT TK-EuroAmerican Journal of Sport Sciences, 2025)
The aim of this study was to find evidence demonstrating that participating in sports activities has an impact on life satisfaction of individuals involved in these activities. The methodology followed the Preferred Reporting Items for Systematic Reviews (PRISMA) technique. Databases was searched using indexing services, including Scopus and Web of Science. A total of 13 articles met the inclusion criteria. The results showed that 1) Physical activity with social interaction and self-efficacy is important for improving life satisfaction and physical well-being across various age groups. 2) It is important to manage stress and fatigue that may arise, even though physical activity and good nutrition improve life satisfaction. 3) Body weight status and gender affect physical literacy and life satisfaction in children and adolescents. 4) Life satisfaction derived from physical activity has a significant long-term impact on health and future care needs. 5) Well-structured physical activity, whether in team practice or individual activities, can enhance life satisfaction and mental health. 6) The quality of experience in physical activity is more important than the duration in improving life satisfaction. By understanding the factors that mediate the relationship between physical activity and well-being, this research can help develop a more comprehensive theory of how physical activity affects mental and physical health.